Hubungan Konten Parenting Di Media Sosial Terhadap Perubahan Perilaku Gaya Pengasuhan Orang Tua Milenial - Rahmi Pramesthi Wulandari; Renistiara Medilianasari (UNIB Press, 2026)
The existence of this parenting content has several impacts on millennial parents who consume it. The purpose of this study is to find out the extent of the relationship between parenting content and changes in parenting styles, parents' way of assessing the credibility of parenting content, the process of adopting existing parenting ideas, and short-term changes in parenting styles. The method used is quantitative with the Spearman's Rho correlation data analysis technique. The research data was processed using SPSS 27.0. Validity and reliability tests were carried out before the questionnaire was distributed to respondents. Next, the Spearman's Rho test was performed on the primary data collected to test the hypothesis. The results showed a significance value (1-tailed) of p < .001, where a value of 0.01 < .005, meaning that H0 was rejected. From these results, it can be explained that parenting content on social media has a positive and significant correlation to changes in parenting styles of millennial parents. The correlation coefficient value was obtained at 0.489, indicating that the influence of variables has a positive direction. The results of this study emphasize that parenting content on social media has a positive impact, one of which is a change in parenting style that prioritizes democratic values. The conclusion of this study shows that the level of correlation strength is sufficient between parenting content on social media and changes in parenting style.